The Effects of Authentic Tasks on Preservice Teachers' Attitudes towards Classes and Problem Solving Skills - (:unkn) unknown (EDAM, 2013)
This study aimed to investigate the effects of authentic tasks on preschool preservice teachers' attitudes towards the course and problem solving skills. The study was designed in accordance with the pretest -posttest control group model. The data were collected by using the Problem Solving Skills Inventory, the Course Attitude Scale, and the Structured Interview Form to obtain participant views about the process. The study was conducted with a total of 100 third-year preservice teachers who were enrolled in the course Special Education Methods I at Marmara University Ataturk Faculty of Education's Preschool Education Department during the 2010-2011 academic year. Of these participants, 35 were in the experimental group, 35 in the 1st control group and 30 in the 2nd control group. The results showed a positive significant difference in the attitudes of the experimental group towards classes and their problem solving skills perceptions at the end of the experiment, while no such difference was observed in the two control groups. The responses to the interview forms included positive views regarding the process of using authentic tasks from the experimental group, but mostly negative views from the two control groups who underwent traditional instruction. The tasks used in the experimental group in order to develop problem solving skills and recognize professional problems and solutions improved preservice teachers' problem solving perceptions and attitudes towards classes.
Keywords: Authentic Learning; Authentic Task; Attitudes towards Classes; Problem Solving; Preschool Education; Preservice Teacher